Dampak Dampak covid-19 terhadap Usaha MIkro, Kecil dan Menengah - Siti Nuzul Laila Nalini (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2021)
The COVID-19 pandemic has an impact on the economy, social and politics of not only big countries but almost all countries in the world. Indonesia is one of the countries affected especially on the economic side. Indonesia, which is dominated by Micro, Small and Medium Enterprises (MSMEs), needs to pay special attention to this sector because the contribution of MSMEs to the national economy is quite large. This journal aims to analyze the impact of the COVID-19 pandemic on the existence of MSMEs in Indonesia and how solutions can help MSMEs survive in a COVID-19 pandemic situation.